Pengaruh Penggunaan Media Audio Visual terhadap Kemampuan Menulis Cerpen di SMPN 19 Padang - Maroha, Subur; Basri, Irfani; Afnita, Afnita (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2013)
This article was written to detect the influence of audio visual media concerning short story writing skill of class VII students of SMPN 19 Padang. The data of this research were the result of the short story writing final test. The data were collected by giving short story writing test through audio visual media and without audio visual media. The hipotesis tested by using test-t formula. The result indicated that (1) the arithmetic average of the students’ short story writing skills experiment group were 72,53; (2) the arithmetic average of the students’ short story writing skills control group were 62,04; and (3) according to test-t’s result, can be concluded that there was a significant influence of the used of audio visual media to the short story writing skill of class VII students of SMPN 19 Padang.